2018
DOI: 10.1002/2017jf004469
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Shallow Taliks on Permafrost Thaw and Active Layer Dynamics in Subarctic Canada

Abstract: Measurements of active layer thickness (ALT) are typically taken at the end of summer, a time synonymous with maximum thaw depth. By definition, the active layer is the layer above permafrost that freezes and thaws annually. This study, conducted in peatlands of subarctic Canada, in the zone of thawing discontinuous permafrost, demonstrates that the entire thickness of ground atop permafrost does not always refreeze over winter. In these instances, a talik exists between the permafrost and active layer, and AL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
104
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 103 publications
(114 citation statements)
references
References 68 publications
5
104
0
Order By: Relevance
“…A sharp decrease in liquid volumetric soil moisture indicates soil freezing. Liquid water content of frozen soils at this site typically ranges from 0.15 to 0.2 (Connon et al , ). In both the bog and thawing plateau, ground heat flux (Q G , W/m 2 ) was measured using a ground heat flux plate (Campbell Scientific, HFT3) installed at 5 cm below the ground surface (Figure c,f), calibrated according to the method described by Hayashi et al () and calculated to include heat storage between the ground surface and ground heat flux plate.…”
Section: Micrometeorological Station Datamentioning
confidence: 97%
“…A sharp decrease in liquid volumetric soil moisture indicates soil freezing. Liquid water content of frozen soils at this site typically ranges from 0.15 to 0.2 (Connon et al , ). In both the bog and thawing plateau, ground heat flux (Q G , W/m 2 ) was measured using a ground heat flux plate (Campbell Scientific, HFT3) installed at 5 cm below the ground surface (Figure c,f), calibrated according to the method described by Hayashi et al () and calculated to include heat storage between the ground surface and ground heat flux plate.…”
Section: Micrometeorological Station Datamentioning
confidence: 97%
“…Chasmer et al 2016). The increasing prevalence of taliks at Scotty Creek (Connon et al, 2018) has led other authors to investigate the extent of taliks in other regions (e.g. Lamontagne-Hallé et al, In press), many of whom also report an increase in the number 5 of active flowpaths, especially during the winter months when most hydrological processes were previously assumed to be dormant (Sjöberg et al, 2016;Walvoord et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…In the discontinuous permafrost zone, permafrost thaw involves simultaneous lateral recession of the near vertical sides (which can be significant) (McClymont et al, 2013) of a permafrost body, and lowering of its permafrost table. Connon et al (2018) demonstrated that the development of talik is a kind of "tipping point" that greatly accelerates the rate 30 of permafrost thaw. Specifically, they found that the permafrost below areas with a talik thawed five times faster than areas without a talik, as the unfrozen talik prevents energy loss from the permafrost body to the atmosphere during the winter.…”
Section: Scotty Creek In Transitionmentioning
confidence: 99%
See 2 more Smart Citations